Crises, Financial Leadership, and the Six Stretches for Financial Education. Issue 1 (6th April 2017) - Bruner, Robert F.
Abstract : The former dean of the University of Virginia's Darden School explores how business schools must adapt to prepare future business leaders to assume the leadership responsibilities necessary to respond effectively to financial crises. The article begins with a statement by Milton Friedman and Anna Schwarz in their Monetary History of the United States about the failure of U.S. policy makers to prevent the collapse of the U.S. banking system during the Great Depression. Then turning to the crisis of 2008, the author draws on recent accounts of the leadership—both effective and ineffective—provided by policymakers to support Friedman and Schwartz's contention that the success of countries in responding to crises "depends on the presence of one or more outstanding individuals willing to assume responsibility and leadership." After citing Nassim Taleb's characterization of the financial system as inherently "fragile, " the article offers a number of insights about the kind of leadership that is likely to prove effective in protecting such systems. Using the responses of policymakers like Bernanke, Paulson, and Geithner as examples, the author observes that successful leaders rank priorities and set direction, mobilize collective action, choose whether and how to use the "panoply of tools" at their disposal, and attempt to respond in a comprehensive, coordinated way to all aspects of a crisis using a flexible set of approaches and methods that he identifies as "Ad Hoc‐racy." With such insights in mind, the author goes on to suggest that changes in current research and teaching about leadership are likely to take the form of the following six "stretches": From local to global : "Global" in the context of crises refers to thinking systemically about connectedness and the tendency of trouble to travel within systems of finance. From a single‐discipline to an interdisciplinary focus : As examples, the dynamics of mobilizing collective action can be illuminated by research on group decision‐making and bargaining theory; and process management research holds insights for the conduct of "Ad Hoc‐racy." From passive learning to active learning : Because so much of crisis leadership is a response to contingencies, exercising students' skills in financial "whack‐a‐mole" seems like a valuable complement to more traditional pedagogical styles. Better for students to explore the consequences of bad judgment in the classroom than in the markets. From scholarship about problems of interest to scholarship about problems of consequence : If only because the costs associated with risks to the financial systems are so large, financial leadership is consequential and warrants inquiry. From field mastery to growth of wisdom : Although mastery of the tools and concepts of finance is necessary for a successful career in the field, we need financial leaders who can harness such concepts and analytical insights to sound judgment in the pursuit of larger goals, including, when appropriate, the greatest social good. From preparation for followership to preparation for leadership : The popularity of finance on campuses and the high salaries of finance recruits attest to the value of what higher education delivers in this field. But what the students and recruiters want is preparation for the first job in the field—that is, training that prepares students to follow . We can do better than that.